2021
DOI: 10.51253/pafmj.v71i2.3109
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Refractive Error and Amblyopia in Strabismus in Pediatric Age Group

Abstract: Objective: To see the frequency and compare the type of refractive error and strabismus in amblyopic versus non amblyopic children. Study Design: Comparative cross sectional study. Place and Duration of Study: Armed Forces Institute of Ophthalmology, Rawalpindi, from Jan to Jul 2019. Methodology: The sample population comprised of 250 patients of new or previously diagnosed children with refractive error and strabismus presenting at children eye outdoor patient department of armed forces inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Although this study recorded astigmatism in 10.3% of the participant, a study published in 2018 showed astigmatism frequently present in patients presented to eye OPD with squint [15]. In addition, another study also stated astigmatism as the most common cause of strabismus and amblyopia among children [16].…”
Section: Discussionmentioning
confidence: 71%
“…Although this study recorded astigmatism in 10.3% of the participant, a study published in 2018 showed astigmatism frequently present in patients presented to eye OPD with squint [15]. In addition, another study also stated astigmatism as the most common cause of strabismus and amblyopia among children [16].…”
Section: Discussionmentioning
confidence: 71%